Social media, political efficacy and political participation in Nigeria - Akinyetun, Tope Shola (2022)
Access online through this link: https://www.plarideljournal.org/article/social-media-political-efficacy-and-political-participation-in-nigeria
Keywords: Social media and politics; Political participation; Politics and culture -- Nigeria